Refinements of moment-based cost functions improve prediction of experimental moment profiles in cycling - van Werkhoven, H.; Sommer, H. J.; Martin, P. E. (2008 Annual Meeting (NACOB) Ann-Arbor, 2008)
Many cycling simulations (e.g., Gonzalez & Hull, 1989; Kautz & Hull, 1995) have employed joint moment-based computer models. A common cost function in simulations is based on the sum of squares of ankle, knee, and hip moments (e.g., Kautz & Hull, 1995; Redfield & Hull, 1986). In its simplest form absolute joint moments are used with equal weighting of concentric and eccentric contributions and equal contributions of the three joints. Potential refinements include using net joint moments expressed relative to maximum flexion and extension moment capacities, representing eccentric effort as some fraction of concentric effort, and weighting contributions from the ankle, knee, and hip differently (e.g., Kautz (1992) doubled the relative cost of the knee in cycling simulations). Our purpose was to evaluate the effect of these three refinements on the accuracy of predicting experimentally-derived lower extremity moments for 250 W cycling at 90 rpm. We predicted each of these refinements would result in more accurate lower extremity moment profiles.